2005
DOI: 10.1007/s00244-004-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the Behavioral Response to Kairomones by the Parasitoid Wasp Leptopilina heterotoma Surviving Insecticides

Abstract: Hymenopterous parasitoids are key species involved in the regulation of insect populations. Kairomone perception is an important step leading to host parasitization. The massive use of insecticides induces environmental pollution that can interact with the reproduction of parasitoids. In this work, we have determined the sublethal effects of two insecticides, an organophosphorus (chlorpyrifos) and a pyrethroid (deltamethrin), on the arrestment, by host kairomones, of female parasitoids surviving an LD 20 for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
0
20
0
3
Order By: Relevance
“…For example, Komeza et al (2001), studied Leptopilina boulardi (Hymenoptera: Figitidae) females exposed to the LD20 of the organophosphate chlorpyrifos and found them to be less efficient in finding host patches marked with kairomones, and exhibit longer patch residence times. In contrast, Delpuech et al (2005) found that the congeneric Leptopilina heterotoma Thomson females responded to kairomones of Drosophila with greater arrestment following contact with chlorpyrifos and deltamethrin at LD20. Thus, either inhibitive or stimulative (hormoligosis) effects of neurotoxic insecticides may be observed at sublethal doses, depending on the insecticide and species of insect.…”
Section: Discussionmentioning
confidence: 79%
“…For example, Komeza et al (2001), studied Leptopilina boulardi (Hymenoptera: Figitidae) females exposed to the LD20 of the organophosphate chlorpyrifos and found them to be less efficient in finding host patches marked with kairomones, and exhibit longer patch residence times. In contrast, Delpuech et al (2005) found that the congeneric Leptopilina heterotoma Thomson females responded to kairomones of Drosophila with greater arrestment following contact with chlorpyrifos and deltamethrin at LD20. Thus, either inhibitive or stimulative (hormoligosis) effects of neurotoxic insecticides may be observed at sublethal doses, depending on the insecticide and species of insect.…”
Section: Discussionmentioning
confidence: 79%
“…Para o sucesso de um programa de manejo fitossanitário, a integração de produtos químicos com o controle biológico é necessária . Assim, estudar a seletividade dos agrotóxicos é importante, para que se tenha sucesso na sua associação com os inimigos naturais das pragas (Delpuech et al, 2005).…”
Section: Introductionunclassified
“…In face of these results, the authors hypothesize that the sublethal effect of deltamethrin on host foraging may decrease T. basalis efficacy in controlling N. viridula. Delpuech et al (2005) also found that deltamethrin increased the arrestment response of Leptoplilina heterotoma (Hymenoptera: Figitidae) to host cues and reduced their linear speed. The authors explained that the observed increase in the arrestment response is coherent with pyrethroid intoxication, given that deltamethrin induces a prolongation of nervous stimulations each time neurons are stimulated by the perception of host cues.…”
Section: Mobility and Orientationmentioning
confidence: 88%